Seismic vulnerability and risk analysis of the old building stock at urban scale: application to a neighbourhood in Lisbon - Lamego, Paula (2017)
The old buildings represent an important fraction of the urban fabric of the cities, which have implicit societal issues, like safety. This work deals with the seismic vulnerability assessment and risk analysis of the old building stock, with application to a neighbourhood in Lisbon. The studied neighbourhood includes three frequent building typologies in Portugal, i.e. stone masonry, "Placa" and RC buildings. Reference buildings for each typology were numerically modelled using the equivalent frame method. Pushover analysis was then performed to derive the vulnerability characteristics of the reference buildings and more general building classes, i.e. capacity and fragility curves, in order to assess the seismic vulnerability of the buildings and perform a seismic risk analysis. This last analysis was performed to estimate the building damages and the economic and life losses for different earthquake scenarios. Most of the studied buildings are found to be unsafe to the considered seismic actions and will suffer severe damages with associated large losses.